Active learning with research based on three principles of higher education - Istiningsih, Istiningsih; Unruh, Thomas; Sutrisno, Sutrisno; Kurniawati, Urip Meilina (Intelektual Pustaka Media Utama, 2024)
This study aims to determine how using an active learning model based on the three higher education principles can improve students' active learning. Qualitative research methods were applied in this study, with data collection through interviews, literature study, and observation. The results showed that active learning based on the three higher education principles was included in the